RARE CAUSES OF GASTROINTESTINAL BLEEDING IN CHILDREN (Herald of the National Children's Medical Center, 2024)
Gastrointestinal bleeding (GCC) is one of the urgent problems of emergency surgery. The main diseases that cause gastrointestinal bleeding in children are well studied. However, in clinical practice, we have encountered several observations of a long-term diagnostic search for the source of gastrointestinal bleeding.